Determination of Particles and Minerals Content in Soft Clay Soil of the Mekong Delta Coastal Provinces, Southern Vietnam for Inorganic Adhesives Stabilization - Nụ, Nguyễn Thị; Toan, Do Minh; Phi, Hong Thinh; Son, Bui Truong (Iraqi Journal of Science, 2020)
The paper aims at investigating the content of particles and minerals of soft clay soil in the Mekong Delta coastal provinces, southern Vietnam, as well as improving soil stability using inorganic adhesives, i.e.lime and cement-based stabilization. To study the composition of soft clay soil, a series of different laboratory methods were carried out and revealed various characteristics related to mineral composition, pH value, soluble salt content, and grain particle composition of soft clay soils. The results demonstrated five soil subtypes, namely high – saline soil (S2), low-saline soil (S1), acid sulfate soil (A), acid sulfate - saline soil (S-A), soil without salt andacid sulfate content (S0- A0). The soft clay soil (C) included 5 subtypes, which were C-S2, C-S1, C-A, C-AS, and C-S0-A0, whereas the soft sandy clay soil (SC) included three subtypes, namely SC-S2, SC- S1, and SC-S0-A0. Analysis of the above results showed that the high - saline soil, acid sulfate soil, and acid sulfate - saline soil are not suitable for lime and cement stabilization. This observation was illustrated by the initial experiment of cement – soil mixture properties.